Personalized Risk Assessment and Treatment in Ruptured Isolated Posterior Spinal Artery Aneurysm: A Rare Case and Systematic Literature Review - Elisa Garbin; Nicola Cavasin; Luca Basaldella; Salima Magrini (Journal of Personalized Medicine, 2026)
Background: Ruptured isolated spinal artery aneurysms (SAAs) are not common. Posterior spinal artery aneurysms (PSAAs) are less common. Either is rarely the cause of spontaneous spinal subarachnoid hemorrhage (sSAH). Due to a few published reports, the natural course, diagnosis and optimal therapeutic strategy remain debatable and challenging. We report the case of a 60-year-old male presenting with lumbar and abdominal pain, which swiftly became associated with headache, photophobia and worsening neck pain. Spinal MRI revealed an intradural hemorrhage collection from the T9 level to the T10 level; the spinal DSA confirmed a fusiform dissecting PSAA originating from the T11 level. He was managed conservatively and recovered completely. We have reviewed the few cases reported in the literature. Results: Except for the present case, there are 29 reported cases of isolated PSAAs and 69 cases of isolated SAAs. The patients’ ages ranged from 16 to 88 years, and common presenting symptoms were headache and back/abdominal pain. The PSAAs were commonly located at the lower thoracic level or lumbar level. The most common PSAA treatment was surgery; among the 29 cases, 85% reported favorable outcomes regardless of the type of treatment. Conclusions: Ruptured spinal artery aneurysms are prone to spontaneous thrombosis. Given the lack of standardized guidelines, a personalized medicine approach is essential, requiring a detailed, patient-specific risk assessment. Conservative management could be an appropriate treatment option with a favorable outcome. Further understanding may help guide future clinical decision-making and tailored treatment planning according to patient-specific features.